Ethylene absorption sachets in postharvest of 'Royal Gala' apples sachês absorvedores de etileno na pós-colheita de maçãs 'Royal Gala' - do Amarante C.V.T.* (2009)
The reduction of ethylene levels in the storage environment is important for postharvest preservation of fruit quality. This research was carried out to assess the effects of ethylene absorption with sachets containing pellets (10g) impregnated with potassium permanganate (KMnO4) on postharvest quality preservation of 'Royal Gala' apples under refrigerated and ambient temperature storage. The addition of one or two sachets of product, for fruits packed in standard cartons boxes (18kg of fruits), lined with high density polyethylene film (30μm), reduced ethylene inside the package during two months of conventional cold storage (at 0±0.5°C/90-95% RH). This led to a better retention of skin background color and flesh firmness and a smaller increase of soluble solids content in the fruits, especially after one week of shelf life (20±4°C/70-80% RH). Under ambient temperature, the use of one sachet per box reduced ethylene concentration inside the package and retarded fruit ripening compared to the control treatment. These effects were more evident in fruit harvested in a less advanced maturity stage. The results show that ethylene absorption with KMnO4 is a viable alternative to preserve postharvest quality of 'Royal Gala' apple, immediately after fruit harvest, during cold storage transportation of exported fruit, as well as during fruit retail at ambient temperature.